Industrialised Building Systems (IBS) in Malaysian construction industry / Dr Hjh Hamimah Adnan and Nor Azmi Ahmad Bari - Adnan, Hamimah; Ahmad Bari, Nor Azmi (Faculty of Architecture, Planning and Surveying, 2007)
This study focuses on cost estimating techniques which commonly used by Quantity Surveyor and factors that influencing the construction cost in the Malaysian construction industry. Early stage cost estimating is one of the most important activities during project planning. Every project begins its life from concepts proposed by the owner and refined by the designers. This is due to the nature of planning, which occurs at the early stages of project where limited information is available and many factors affecting the project costs are unknown. Future uncertainties plaguing the construction industry further complicate the planning processes. As such, this study investigates the incidence-of-use of current practices of cost estimating techniques in the construction industry in Malaysia. It determines whether the call for a 'paradigm shift' from traditional models towards a general use of the nontraditional methods or new wave method is achieved. This provides the platform for developing a model that can be used in the early stage of cost planning.